KECERNAAN PROTEIN KASAR DAN LEMAK KASAR PADA SAPI PERAH PERANAKAN FH (FRIESIAN HOLSTEIN) YANG DIBERI PAKAN LENGKAP BERBASIS TEBON JAGUNG - Polii, Diwi N.Y.; Waani, M. R.; Pendong, A. F. (ZOOTEC, 2020)
THE DIGESTIBILITY OF CRUDE PROTEIN AND CRUDE FAT ON FRIESIAN HOLSTEIN (FH) DAIRY COW FED COMPLETE FEED BASED ON CORN FORAGE. This study aims to determine the intake and digestibility of the crude protein and crude fat of complete feed based on corn forage. 14 FH dairy cows with 300-400 kg of weight were used in this study. This study was arranged in two treatment groups according to t-test (assuming unequal varience). The treatments consisted of Ra = 30% concentrate + 70% corn forage and Rb = 30% concentrate + 35% corn forage + 35% king grass. The variables measured were crude protein and crude fat intakes, and crude protein and crude fat digestibilities. t-test analysis results showed, the crude protein intake of Ra (934.23 grams/head/day) was not significantly different (P>0.05) from Rb (924.20 grams/head/day), as well as the crude fat intake of Ra (332.93 grams/head/day) was also not significantly different (P>0.05) form Rb (350.66 grams/head/day). The digestibility of crude protein in Rb treatment (85.34%) was significantly (P<0.05) higher than Ra (82.18%), while the digestibility of crude fat in Rb treatment (88.90%) was highly significant different (P<0.01) from Ra (84.31%). It is concluded that complete feed consisting of concentrate, corn forage and king grass has better crude protein and crude fat digestibilities than the other one that just consisting concentrate and corn forage.Â Keywords: digestibility, crude protein, crude fat, complete feed, FH cows.